Age‐Related Plasticity Integration in Male Cicadas Tettigetta isshikii: Are Adult Cicadas Capital Breeders? - Jiman Heo; Chang S. Han (Ecology and Evolution)
ABSTRACT Labile traits, such as behavioural, physiological traits or body mass, vary within an individual either over time or across environments. Such changes within an individual can be linked across traits, forming within‐individual trait correlations. These correlations are particularly expected when ageing causes changes in the expression of multiple traits. Moreover, the direction of these correlations depends on mechanisms that explain age‐related changes in each trait, such as physiological deterioration or changes in future fitness expectations. Therefore, assessing within‐individual trait correlations offers insights into trait‐specific ageing patterns, their integration and age‐related reproductive strategies. Here, we tracked individual male cicadas (Tettigetta isshikii) in their natural habitat, repeatedly assessing their plant use (narrow‐leafed vs. large‐leafed plants), calling activity and body mass. The results revealed that male cicadas lost mass, increased calling activity and a preference for narrow‐leafed plants as they aged. This integration of age‐related plasticity led to negative within‐individual correlations between body mass and behaviours. Considering that adult cicadas consume nutritionally poor xylem sap, the negative within‐individual correlations between body mass and risk‐taking behaviour suggest that T. isshikii males follow a capital breeding strategy rather than an income breeding strategy. As adult cicadas may use up the energy stored during the nymph stage, an age‐related increase in energetically demanding calling activity could cause an age‐related decrease in body mass. The terminal investment hypothesis could also explain the age‐related increase in calling activity and the preference for narrow‐leafed plants. Therefore, we emphasise the importance of individual‐level tracking studies in the wild to achieve a comprehensive understanding of the life‐history strategies and behavioural ecology of a study animal.